Chemical interaction between the larva of a dipteran parasitoid and its coleopteran host: A case of exploitation of the communication system during the searching behaviour? - Groba, Hernán Federico (2012)
The robber fly Mallophora ruficauda is one of the principal apicultural pests in the Pampas region of Argentina. As adults, the flies prey on honey bees and other insects; while, as larvae, they parasitize scarab beetle larvae. Females of M. ruficauda lay eggs away from the host in tall grasses. After being dispersed by the wind, larvae drop to the ground, where they dig in search of their hosts. It is known that second instar larvae of M. ruficauda exhibit active host searching behaviour towards its preferred host, third instar larva of Cyclocephala signaticollis, using host-related chemical cues. Furthermore, previous works show that these chemical cues are produced in the posterior body half of hosts. However, the precise anatomical origin of these cues and whether they mediate any behaviour of C. signaticollis larvae remains yet unknown. In order to determine the precise origin of the chemical cue, we carried out olfactometer assays with different stimuli of extracts of the posterior C. signaticollis body half. Additionally, we tested whether C. signaticollis is attracted to any of the same extracts as in the previous experiments. We found that both second instar of M. ruficauda and third instar of C. signaticollis are attracted to extracts of the fermentation chamber (proctodeum). This is the first report of attraction of conspecific larvae in scarab beetles. We discuss a possible case of system communication exploitation in an immature parasitoid-host system.